Loading Range for the Development of Peak Power in the Close-Grip Bench Press versus the Traditional Bench Press - Robert G. Lockie; Samuel J. Callaghan; Ashley J. Orjalo; Matthew R. Moreno (MDPI AG, 2018)
The close-grip bench press (CGBP) is a variation of the traditional bench press (TBP) that uses a narrower grip (~95% biacromial distance) and has application for athletes performing explosive arm actions where the hands are positioned close to the torso. Limited research has investigated CGBP peak power. Twenty-six strength-trained individuals completed a one-repetition maximum TBP and CGBP. During two other sessions, subjects completed two repetitions as explosively as possible with loads from 20% to 90% for each exercise, with peak power measured by a linear position transducer. A factorial ANOVA calculated between- and within-exercise differences in peak power. Partial correlations controlling for sex determined relationships between absolute and relative strength and peak power load. Peak power for the TBP occurred at 50% 1RM, and 30% 1RM for the CGBP. There were no significant (p = 0.680) differences between peak power at each load when comparing the TBP and CGBP. For the within-exercise analysis, there were generally no significant differences in TBP and CGBP peak power for the 20–50% 1RM loads. There were no significant relationships between strength and peak power load (p = 0.100–0.587). A peak power loading range of 20–50% 1RM for the TBP and CGBP is suggested for strength-trained individuals.